A Few Provisional Observations Concerning Gabriel Josipovici's Story 'Steps'. Issue 1 (1st March 2019) - Jarfe, Günther
Abstract : This article tries to elucidate Gabriel's story 'Steps' to some extent. Here, as elsewhere, the narrator's deliberate failure to clearly separate actual from imaginary facts and incidents causes problems of understanding. Initially, we are told that the protagonist has long been living in Paris. A little later, however, we hear that he has moved to Wales with his second wife. So where does the man live? While other stories remain ambiguous throughout, 'Steps' seems less impenetrable. The protagonist, we learn, often indulged fantasies when he went for his strolls in Paris and is quoted as saying 'Going up and down steps lets the mind float free'. When at the end of the story the narrative suddenly shifts to the present tense – '…he climbs the steps of the rue St. Julien' – this seems to suggest that most of the story represents aspects of the protagonist's 'alternative lives', as envisaged during his walks.